2012
DOI: 10.1002/fuce.201100115
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation and Parametric Optimization of a Proton Exchange Membrane Fuel Cell/heat‐driven Heat Pump Hybrid System

Abstract: With the help of the current models of proton exchange membrane (PEM) fuel cells and three-heat-source heat pumps, a generic model of a PEM fuel cell/heat-driven heat pump hybrid system is established, so that the waste heat produced in the PEM fuel cell may be availably utilized. Based on the theory of electrochemistry and non-equilibrium thermodynamics, expressions for the efficiency and power output of the PEM fuel cell, the coefficient of performance and rate of pumping heat of the heat-driven heat pump, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
3
0
1
Order By: Relevance
“…On the other hand, the limiting current due to the Pt/C electrocatalyst was revealed to be 3.84 mA cm 2 (based upon the geometric area) in the ORR. This parameter was enhanced to 5 mA cm 2 for the (1:3) Ag@Pt/rGO material. These values indicated that the di usion-limiting currents were strongly a ected by the core-shell structure and the supporting materials for the Pt catalyst.…”
Section: Electrochemical Measurementsmentioning
confidence: 94%
See 2 more Smart Citations
“…On the other hand, the limiting current due to the Pt/C electrocatalyst was revealed to be 3.84 mA cm 2 (based upon the geometric area) in the ORR. This parameter was enhanced to 5 mA cm 2 for the (1:3) Ag@Pt/rGO material. These values indicated that the di usion-limiting currents were strongly a ected by the core-shell structure and the supporting materials for the Pt catalyst.…”
Section: Electrochemical Measurementsmentioning
confidence: 94%
“…Ultimately, the MEA was assembled with the GDL for the electrochemical tests in a 6.25 cm 2 Paxi-tech single fuel cell [57]. Accordingly, both anode and cathode contained platinum loadings of 0.5 mg cm 2 (MEA-1) and a 1:3 mass ratio of Ag@Pt/rGO (MEA-2) all with a Na on loading of 0.9 mg cm 2 .…”
Section: Fuel Cell Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…、燃料电池-制冷机 [55,56] 、燃料电池-热泵 [57] 、 燃料电池-热电发电机 [58,59] 、燃料电池-真空热离子混 合系统 [60] 、光子增强热离子发电机 [61,62] 和量子点热 机 [63] 各种系统的最优性能. [68] 在给定时间约束下, 对间歇反应器中的nA mB 型化学反应进行了产率最大化研究, 得到了最优的反 应体积和温度最优构型.…”
Section: 被应用到各类能量系统的性能优化中 取得了 重要研究进展 研究对象包括斯特林循环unclassified